Utility of CT imaging in a novel form of high‐dose‐rate intraoperative breast radiation therapy. Issue 6 (13th August 2018) - Hassinger, Taryn E; Showalter, Timothy N; Schroen, Anneke T; Brenin, David R; Berger, Adam C; Libby, Bruce; Showalter, Shayna L
Abstract: Introduction: Intraoperative radiation therapy (IORT) is an alternative to whole breast radiation following breast conserving surgery. Conventional breast IORT is limited by lack of cross‐sectional imaging. In response, our institution developed Precision Breast IORT (PB‐IORT) which utilizes intraoperative computed tomography (CT) images for confirmation of brachytherapy applicator placement and for treatment planning. The purpose of this study was to determine the utility of CT imaging in PB‐IORT in the first 103 patients treated in two prospective clinical trials. Methods: We retrospectively reviewed the first 103 patients treated with PB‐IORT. All patients underwent breast surgery and placement of a multi‐lumen brachytherapy applicator. Patients had a CT scan followed by high‐dose‐rate (HDR) brachytherapy. Endpoints were the number of patients having more than one CT during PB‐IORT and the number of treatment plans having image‐based modifications. Results: After initial CT scan, 27 patients (26.2%) had findings prompting surgical applicator adjustment. One patient underwent an additional scan to localize a biopsy clip and aid in excision to negative margin. Eighty‐one patients (78.6%) had dosimetry modifications based on CT findings with 36 plans (35.0%) adjusted to protect the skin or chest wall and 45 plans (43.7%) to protect both the skin and chest wall. Conclusions: Computed tomography findings prompted treatment alterations in the majority of patients treated with PB‐IORT to enhance tissue conformity and to sculpt the radiation dose away from normal tissues. CT imaging is unique to PB‐IORT. These findings suggest the potential clinical superiority of PB‐IORT given its allowance for patient‐specific alterations.